INFLUENCE OF PEAT WATER ON MECHANICAL PROPERTIES OF COCONUT SHELL AND FLY ASH BASED CONCRETE - Yulin Patrisia; Topan Eka Putra (Jurusan Pendidikan Teknologi dan Kejuruan, FKIP, Universitas Palangkaraya, 2019)
This study aimed to determine the influence of peat water on the mechanical properties of the paving block (compressive strength and water absorption) using coconut shell waste and fly ash as raw material. The background of the research were the lack utilization of fly ash, preparation for the handling and utilization of fly ash from power station at Pulang Pisau and Tumbang Kajuei (under construction), and the utilization of coconut shell to be more effective and economical. Paving block specimens were immersed in peat water to determine the effect of peat water and the rest were immersed in plain water. This experiment used fly ash as a partial replacement of cement and 2% coconut shell as a partial replacement of fine aggregate. The results of the analysis showed that: (a) Paving block using fly ash and coconut shells which were immersed in plain water experienced the increase in compressive strength and the decrease in water; (b) Paving block using fly ash and coconut shells soaked in peat water showed that by the increase of age, compressive strength was decrease and water absorption was increase; (c) The compressive strength of paving block specimens immersed in plain water and peat water showed relatively similar values at 7 and 28 days age, (d). Water absorption in paving block specimens soaked both in plain water and peat water showed relatively similar values at 7 days age, but at 28 days age the specimens immersed in peat water had greater water absorption.